1974
DOI: 10.1203/00006450-197412000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Glucagon Substrate Interrelations in the Fetal Sheep

Abstract: Extract METHODS AND MATERIALSTwenty-four studies were conducted in 14 sheep fetuses to Fourteen healthy date-bred pregnant ewes with gestational investigate the pancreatic islet a! and /3 cell responses to ages ranging from 100-145 days were studied. The chronic substrate infusions. The studies were conducted between 100 indwelling catheter preparation was utilized and has been days gestation and near term, using indwelling vascular described previously (14). Briefly, a laparotomy through a left catheters for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Ep stein et al [12] found no increase in fetal glu cagon in the rhesus monkey made glucose intolerant with streptozotocin. Similar obser vations have been made in the fetal lamb, in which the concentration failed to change in response to fetal glucose infusion [15], In studies of chronic maternal fasting in the ewe, we found no significant change in the concentration of glucagon in fetal plasma during short-term fasting [37], but did find a trend towards an increased glucagon concen tration with a prolonged fast (more than 6 days) [36]. The purpose of this study was to investigate the effect of exogenous glucagon on fetal glucose, fructose and insulin in the sheep.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Ep stein et al [12] found no increase in fetal glu cagon in the rhesus monkey made glucose intolerant with streptozotocin. Similar obser vations have been made in the fetal lamb, in which the concentration failed to change in response to fetal glucose infusion [15], In studies of chronic maternal fasting in the ewe, we found no significant change in the concentration of glucagon in fetal plasma during short-term fasting [37], but did find a trend towards an increased glucagon concen tration with a prolonged fast (more than 6 days) [36]. The purpose of this study was to investigate the effect of exogenous glucagon on fetal glucose, fructose and insulin in the sheep.…”
Section: Introductionsupporting
confidence: 48%
“…As with insulin, glucagon has been identified in the fetal pancreas from early in gestation and the evidence would suggest that glucagon is not transferred across the placenta [10,15]. Chez et al [10] have shown that fetal hypo glycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Epstein et al (10) found no increase in fetal glucagon in the rhesus monkey made glucoseintolerant with streptozotocin. Fiser et al (12) as in monkey and man is significantly less than in the maternal blood. The data in this study would suggest that glucagon is not an important regulator of fetal metabolism during maternal starvation because there was no significant change in the glucagon concentration in the fetus throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein et al (7) found no increase in fetal glucagon in the rhesus monkey made glucose intolerant with streptozotocin. Fiser et al (11) found no in crease in glucagon concentration in response to glucose infusion in the fetus. The concen tration of glucagon in the fetal sheep, as well as in monkey and man.…”
Section: Discussionmentioning
confidence: 99%